Understanding zakat fatwas in Kedah: A Maqasid Al-Shari’ah and Fiqh Al-Waqi’ perspective - Harun, Rabitah; Hussin, Rohayati; Anuar, Azyyati; Manshor, Nurul Mazrah; Fazial, Farahdina; Sadek, Daing Maruak (Journal of Islamic, Social, Economics and Development, 2025)
This study examines Zakat fatwas in Kedah, Malaysia, through the frameworks of maqasid al-shari'ah (higher objectives of Islamic law) and fiqh al-waqi' (understanding of contemporary realities). The central issue is balancing the alignment of zakat rulings with modern socio-economic challenges while adhering to Islamic legal principles. As one of Islam’s Five Pillars, zakat is essential for addressing poverty, promoting social justice, and fostering community well-being. However, its implementation faces complexities due to evolving societal needs and economic changes. This research addresses this gap by evaluating how zakat fatwas in Kedah are formulated and whether they effectively respond to current issues while remaining grounded in Islamic jurisprudence. Objectives of this study include analyzing Zakat fatwas in Kedah for adherence to maqasid al-shari'ah and assessing their relevance. Methodologically, it employs qualitative analysis of fatwas from Kedah's religious authorities. Expected findings offer insights into the alignment of zakat fatwas with Islamic law and adaptation to modern challenges. The study's implications involve informing policymakers and religious authorities in Kedah about the importance of relevant and effective zakat fatwas to address societal needs and contribute to community well-being.